Patriachal Culture's Effects on Women as Reflected on the Basis of Sex (2018) Film - Kamila, Zahra (Linguistic, English Education and Art (LEEA) Journal, 2024)
Gender stereotypes appear in the media, such as in films when male rulers typically govern female minority groups; this situation is known as patriarchal culture. The patriarchal culture emphasizes the need to study literature through film as a product of a culture that depicts discrimination against women through figures and storylines. This research method applies descriptive qualitative research to collect and analyze how patriarchal culture's effects on women and women's attempts against patriarchal culture are reflected in the film On the Basis of Sex (2018) using Radical Feminism theory from Kate Millet’s prespective. Research findings highlight that the film On the Basis of Sex depicts patriarchal culture effects as women's access to education, job opportunities, women's behavior, and freedom in public spaces. This study further investigates women's attempts against patriarchal culture through the female characters in this film, namely their challenges with education, carieer, self-confidence, and skills. As a result, this study's involvement reveals insight into the value of media depiction of gender issues and helps to advance the gender equality movement for women. Keywords: Gender Stereotype, Radical Feminism, Patriarchal Culture, Women